2002
DOI: 10.4269/ajtmh.2002.66.533
|View full text |Cite
|
Sign up to set email alerts
|

Comparative safety and immunogenicity of two yellow fever 17D vaccines (ARILVAX and YF-VAX) in a phase III multicenter, double-blind clinical trial.

Abstract: Abstract. Yellow fever (YF) is a significant health problem in South America and Africa. Travelers to these areas require immunization. The United States, infested with Aedes aegypti mosquitoes, is at risk of introduction of this disease. There is only a single U.S. manufacturer of YF 17D vaccine, and supplies may be insufficient in an emergency. A randomized, double-blind outpatient study was conducted in 1,440 healthy individuals, half of whom received the U.S. vaccine (YF-VAX) and half the vaccine manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
111
2
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(129 citation statements)
references
References 26 publications
8
111
2
2
Order By: Relevance
“…That converges with data from two previous studies. 5,10 Others 14,18 found small elevations in AST, ALT and GGT, but lacked unvaccinated controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…That converges with data from two previous studies. 5,10 Others 14,18 found small elevations in AST, ALT and GGT, but lacked unvaccinated controls.…”
Section: Discussionmentioning
confidence: 99%
“…3 The frequency of signs and symptoms on the injection site reported in the literature varied from nil to 39%. 5,7,[9][10][11]14,15,17,18,20,22,23 In all studies, pain on the site of injection was the most frequently reported local adverse event. The highest frequencies of adverse events were based on diaries, which could inflate the frequency by stimulating reports of trivial signs/symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Japanese encephalitis virus and Yellow Fever, where the accepted vaccine-elicited correlate of immunity is virus-neutralizing antibody. [28][29][30][31] Confirmation that virus neutralizing antibody is a correlate of dengue immunity is most likely to come Sabin demonstrated in the post-war era how infection with one serotype gave long-lasting protection to that specific serotype (homotypic immunity) and short-lived protection against the other serotypes (heterotypic immunity). 33 The basis for homotypic immunity is believed to be virus-neutralizing antibodies.…”
Section: The Humoral Immune Response and Antibody-dependent Enhancementmentioning
confidence: 99%